Opening Remarks at the 2019 Annual Meetings Opening Press Conference - Malpass, David (World Bank, Washington, DC, 2020)
David Malpass, President of the World Bank Group, highlighted the urgent priorities for discussion with shareholders. Global growth is slowing. Investment is sluggish, manufacturing activity is soft, and trade is weakening. The challenges of climate change and fragility are making poor countries more vulnerable. This backdrop makes our goals of reducing extreme poverty and boosting shared prosperity even harder. He suggested that with the right mix of policies and structural reforms, countries can unleash growth that's broadly shared across all segments of society. He spoke about how the Bank is helping countries build strong programs tailored to the unique circumstances of their economies. He highlighted the importance of education. He mentioned the proposed IDA replenishment, and reaffirmed commitment to projects on climate and on gender inclusion. In conclusion, he said that the well-designed structural reforms are needed to unlock growth and build the foundations for future prosperity.